2017
DOI: 10.1111/ene.13410
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial elastance is increased in idiopathic intracranial hypertension

Abstract: As calculated by clinically accessible indices, our study provides evidence that intracranial elastance is increased in IIH, reflecting a novel insight into disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The PVI is inversely related to craniospinal elastance (E). PVI has reflected an increased elastance in patients with idiopathic intracranial hypertension . Conversely, an association has been previously reported between spontaneous intracranial hypotension and connective tissue disorders, where dysfunctional tissue elasticity is present …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The PVI is inversely related to craniospinal elastance (E). PVI has reflected an increased elastance in patients with idiopathic intracranial hypertension . Conversely, an association has been previously reported between spontaneous intracranial hypotension and connective tissue disorders, where dysfunctional tissue elasticity is present …”
Section: Introductionmentioning
confidence: 92%
“…In addition to the routinely reported lumbar puncture indices, it has been hypothesized that the change in CSF pressure relative to the volume withdrawn may be more reflective of PDPH susceptibility . In 1925, Alpers observed, “the outstanding feature in the cases in which there was a headache, however, was the marked fall in the spinal fluid pressure after the withdrawal of fluid.” The relationship between OP, closing pressure (CP) and volume removed (V) is captured by the pressure‐volume index (PVI) . The PVI is inversely related to craniospinal elastance (E).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, I think that the authors should mention whether the association between intracranial elastance and opening pressure was analyzed, which probably constitutes a more crucial point for interpretation of the study results. The authors state that the pressure-volume index is a variable that has been shown to be independent of ICP [1,2]. Therefore, I think that it was redundant to analyze the correlation between the pressure-volume index and cerebrospinal fluid removal opening pressure, which was negative as expected.…”
mentioning
confidence: 96%
“…I read with great interest the article by Chisholm et al [1] in which they found increased intracranial elastance in their patient group of idiopathic intracranial hypertension (IIH) and discussed some crucial hypotheses in this setting. I think that the starting point used for the study, which is a hypothesis opposite to the previous explanation that discusses the influence of compliant dura in patients with spontaneous intracranial hypotension, is cleverly figured and original.…”
mentioning
confidence: 99%
“…New strategies to improve service provision with accelerated diagnosis and treatment are being employed, e.g., through telemedicine , a model that appears successful. Neurological involvement in medicine remains active across a large spectrum of presentations . Novel mutations in adult‐onset leukoencephalopathy and the spinocerebellar ataxias and the search for biomarkers in neurological disease are some examples of the involvement of neurology research across this spectrum.…”
mentioning
confidence: 99%